Evaluation of groundwater recharge in arid and semiarid regions (case study of Dibdiba formation in Karballa-Najaf plateau) - Ramadhan, Ahmad; Ali, Mukdad; Al-Kubaisy, Raffia (Iraqi Journal of Science, 2024)
The process of recharge the groundwater is the key factors that need to be addressed as is the foundation upon which the process of groundwater use and management properly, especially in arid and semi-arid, like Iraq, so the values of groundwater recharge calculated vary depending on the method used in the calculation and the more factors calculated in the process of calculating the values of groundwater recharge increased margin of error in these values. In this study were selected four methods to calculate the value of recharge for groundwater (fluctuating water table, water balance of the basin, numerical modeling, and balance of chloride ion mass in unsaturated zone) was applied in the Plateau area of Karbala (Dibdiba formation) has given these methods produce different results to the values of groundwater recharge. has given way balance chloride ion mass in the unsaturated zone give a results are closer to reality through compering with the volume of water that inventories renewed.